A new species of Gutierrezia (Asteraceae, Astereae, Solidagininae) from Argentinian Patagonia - Ratto, Francisco; Bartoli, Adriana (Phytotaxa, 2016)
A new species, Gutierrezia chubutensis (Asteraceae, Astereae, Solidagininae) from Florentino Ameghino in Chubut Province, Argentina is described and illustrated. It is distinct from its congeners in Patagonia because of its height (over 50 cm), larger elliptical leaves and numerous heads with yellow flowers and involucre terete or terete-turbinate. A key to differentiate the new species from the other Patagonian species of Gutierrezia is provided.